Transparent glass composite for ionizing radiation detection and imaging - Xiaoyun Xu; Xinyi Liu; Xinyue Chen; Huihong Lin (Journal of Materials Research and Technology)
Accurate detection of ionizing radiation is a crucial area of research in science and technology. The development of scintillating materials that offer high detection efficiency and simple processing methods presents a significant challenge. This study presents a series of transparent glass composite scintillators designed for ionizing radiation detection and imaging. An in-situ crystallization method has been employed to create transparent glass composites embedded with various scintillating units (CaF2, SrF2, and BaF2). A comprehensive comparison of the optical and scintillation properties revealed a substantial improvement in radiation detection performance. The underlying physical mechanisms responsible for this enhanced performance were explored, and the potential applications of these composites in X-ray monitoring and radiation imaging were demonstrated. The results suggest that these transparent glass composite scintillators are a promising option for ionizing radiation detection, offering excellent performance and ease of fabrication.